Spatially distinct, temporally stable microbial populations mediate biogeochemical cycling at and below the seafloor in hydrothermal vent fluids. (15th December 2017) - Fortunato, Caroline S.; Larson, Benjamin; Butterfield, David A.; Huber, Julie A.
Summary: At deep‐sea hydrothermal vents, microbial communities thrive across geochemical gradients above, at, and below the seafloor. In this study, we determined the gene content and transcription patterns of microbial communities and specific populations to understand the taxonomy and metabolism both spatially and temporally across geochemically different diffuse fluid hydrothermal vents. Vent fluids were examined via metagenomic, metatranscriptomic, genomic binning, and geochemical analyses from Axial Seamount, an active submarine volcano on the Juan de Fuca Ridge in the NE Pacific Ocean, from 2013 to 2015 at three different vents: Anemone, Marker 33, and Marker 113. Results showed that individual vent sites maintained microbial communities and specific populations over time, but with spatially distinct taxonomic, metabolic potential, and gene transcription profiles. The geochemistry and physical structure of each vent both played important roles in shaping the dominant organisms and metabolisms present at each site. Genomic binning identified key populations of SUP05, Aquificales and methanogenic archaea carrying out important transformations of carbon, sulfur, hydrogen, and nitrogen, with groups that appear unique to individual sites. This work highlights the connection between microbial metabolic processes, fluid chemistry, and microbial population dynamics at and below the seafloor and increases understanding of the role of hydrothermal vent microbial communities in deep ocean biogeochemical cycles.